Processamento da leitura multilíngue e suas bases neurais : um estudo sobre o hunsriqueano - Limberger, Bernardo Kolling (2018)
The present dissertation reports on a study on the reading processing in speakers of a minority language, predominantly spoken, from the perspective of psycholinguistics in an interface with neuroscience. The investigated language is called Hunsrückisch, a distinct variety of other German varieties, bound historically and by similarity, though. This minority language can enhance the learning of German as a foreign language; however, the question arises as to whether it can trigger the multilingual reading processing (Brazilian Portuguese, Standard German and Hunsrückisch). Therefore, the aim of the present study is to investigate the multilingual reading processing and its neural bases in speakers of Hunsrückisch in comparison to non-speakers. The skills we focused on are phonemic awareness, lexical access, and sentence comprehension. We investigated the influence of the acquisition of Hunsrückisch on the multilingual reading, through accuracy and reading speed processing in three experiments: Phonemic awareness task, Multilingual lexical decision task and Sentence comprehension task. In these experiments, participants were asked to read isolated cognates or in sentential contexts. The participants of the present research are early bilinguals speakers of Hunsrückisch, who were divided in two groups: one composed by multilingual speakers of standard German (GHA) and the other by multilinguals with no knowledge in that language or real beginners (GH). The control group was composed by multilinguals who do not speak German minority languages, but speak Standard German (GA). In addition, a subset of multilinguals participated in the functional magnetic resonance imaging (fMRI) study. The results from the analyzes indicate interinfluences of the languages on the multilingual reading processing. Participants demonstrated higher phonemic awareness for Standard German words, in comparison to the Hunsrückisch words and pseudowords. The results of the statistical tests showed differences between the cognate and non-cognate reading for the minority language group (GHA) when reading isolated words and in sentence comprehension. There was, therefore, a cognate facilitation effect resulting from the sharing of representations between the two languages. There was no effect for reading in Portuguese. The results of the lexical decision task also indicated the most effective construction of the orthographic mental lexicon in Hunsrückisch by the participants who have spelling knowledge of Standard German. The elevated times for sentence reading were modulated by the knowledge in the minority language. In the neuroimaging study, there was more activation of the phonological route for the words in Hunsrückisch and, supposedly, a convergence of neural bases for reading in German and in Portuguese. Through these results, we expect to contribute to the research on minority languages and reading processing, a relationship that is not always perceptible. Psycholinguistic and neuroscientific studies on these languages can offer a relevant contribution to the understanding of multilingualism in its various dimensions and to show other sides of oral and written interaction in linguistic performance. This study may provide implications for the teaching of foreign languages in the multilingual context of southern Brazil and cooperate with the discussion on the maintenance of the minority language in the context of language policies within families and communities.